Availability and characteristics of pulmonary rehabilitation programs in family health centers and hospitals from Chile: Descriptive, retrospective and multicentric study - Méndez, Andrea; Nieto, Carlos; Hidalgo, Gonzalo; Rodríguez Núñez, Iván. (SAGE Publications, 2023)
Objective: To determine availability and characteristics of pulmonary rehabilitation programs performed in 2019 in family health centers and hospitals from Chile. Methodology: A descriptive and retrospective study was designed, considering PR programs operated in 2019. A non-probability and convenience sample was obtained. Availability and characteristics of centers and PR were measured using a questionnaire translated, modified, validated, and sent by email. Results: Out of 80 responses (22.8%), 60% of centers offered PR program, where the lack of time was the greatest barrier. The programs were mainly outpatient, non-personalized, with 10(IQR 4–11) participants, 12 (IQR 12–16) weeks of length, with 2.4 ± 0.6 session/week, and 1 (IQR 1–2) hours/session. Chronic Obstructive Pulmonary Disease (COPD) was the most frequent diagnostic. The programs were mainly comprised of strength training exercises of lower extremity, upper extremity, walking and education. Team was constituted of physiotherapist and physician, with completed training, and directed by a physiotherapist. Modified Borg, MRC dyspnea scale, six-minute walking test and oximetry were used in the assessments. Between 40-80% of patients completed PR, and the major barrier was patient relocated. Conclusion: Increasing PR availability, homogenization of exercises and education, prioritization of assessments supported by scientific evidence, and inclusion of follow-up could be useful to improve the access, quality and results of the treatment, considering new models of PR that allow greater access and acceptability.
Keywords: Pulmonary rehabilitation; Pulmonary diseases; Fisioterapia